Menumbuhkan Budaya Gemar Menabung pada Anak Usia Dini dan Meningkatkan Kreativitas dengan Menghias Celengan - Pramesti, Adista Ika; Assyifa, Mutiya Nur; Khomsatun, Siti; Aryani, Habsyah Fitri (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
Kuliah Kerja Nyata (KKN) or community service program are a form of community service by students as one of implementation the knowledge they have gained directly to the community. This socialization activity has the main target, namely Kandang Panjang Village children aged 2 to 12 years. The aim of this activity is to build an interest in saving in children from an early age through the KKN work program of the Faculty of Economics and Business. This research uses a socialization method by delivering material offline or face to face. Data collection methods include observation, interviews and documentation obtained from various sources related to the topic being studied, as well as literature related to this research. The results of this research indicate that KKN students at the Faculty of Economics and Business use educational resources to increase children's awareness of saving from an early age. The material presented is in the form of the meaning of saving, how to save, the benefits of saving, and at the same time decorating piggy banks as an intermediary to train children's creativity in the hope that the material will be easier for children to understand. The children's enthusiasm during the socialization is a sign of the success of the work program being implemented.